The Impact of Institutional Quality on Monetary Policy in Pakistan (Global Journal of Management and Business Research, 2016)
This study seeks to examine whether the monetary management in Pakistan is conducted under the framework advocated by the Taylor rule. We investigate this question after modifying the Taylor rule to control for the influence of institutional quality on monetary policy. Even after controlling for institutional quality, we find no evidence that the central bank makes use of the Taylor framework in devising monetary policy. Our results also suggest that by and large the focus of the monetary policy has been on containing inflation.
Keywords: institutional quality; monetary management; central bank; taylor rule; ARDL method